2016
DOI: 10.3329/jbau.v12i2.28689
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis of some selected rice genotypes through SSR- based molecular markers

Abstract: An experiment was carried out to assess the genetic diversity of advanced rice (Oryza sativa L.) breeding lines using three SSR markers viz., RM147, RM167 and RM215. Thirty T-aman advanced breeding lines at F 9 generation along with 4 check varieties were assessed. All three primers showed polymorphism. A total of 29 alleles were detected among the rice genotypes with an average of 9.67 alleles per locus. Polymorphism information content (PIC) ranged from 0.47 to 0.88 with an average of 0.71. A dendrogram was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Presence of polymorphism between genotypes revealed that the presence of genetic diversity at the molecular level was high among the selected genotype which implies that, the genetic diversity is more than the morphological diversity and there is ample scope to utilize the material in the breeding programme. These results corroborate the earlier findings of Shahriar et al, (2014), Kundur et al, (2015) and Maruthi (2016) in rice.…”
Section: Identification Of Rice Genotypes Using Ssr Molecular Markerssupporting
confidence: 93%
“…Presence of polymorphism between genotypes revealed that the presence of genetic diversity at the molecular level was high among the selected genotype which implies that, the genetic diversity is more than the morphological diversity and there is ample scope to utilize the material in the breeding programme. These results corroborate the earlier findings of Shahriar et al, (2014), Kundur et al, (2015) and Maruthi (2016) in rice.…”
Section: Identification Of Rice Genotypes Using Ssr Molecular Markerssupporting
confidence: 93%
“…A moderately high level of diversity was found among the 12 loci examined ranging between 0.38 and 0.79 with average of 0.62. The implication of the number of allele diversity and their frequency among the accessions is referred to as polymorphic information content (PIC) (Shahriar et al, 2014). PIC value of each marker is estimated on the (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from these studies are also comparable to this study. Shahriar et al (2014) reported an average PIC value of 0.71 among 34 Bangladeshi Aman rice using 3 SSR markers. In another study, Siddique et al (2016) found a PIC value of 0.90 among 96 Bangladeshi Aman rice employing 8 SSR markers.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from these studies are also comparable to this study. Shahriar et al. (2014) reported an average PIC value of 0.71 among 34 Bangladeshi Aman rice using 3 SSR markers.…”
Section: Discussionmentioning
confidence: 99%